2010
DOI: 10.1093/ejechocard/jeq033
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic strain imaging is superior to conventional non-invasive measures of vascular stiffness in the detection of age-dependent differences in the mechanical properties of the common carotid artery

Abstract: Ultrasonographic 2D-strain imaging is a sensitive method for the assessment of elastic properties in the CCA, being in this respect superior to the conventional measures of vascular stiffness. The method has potential to become a valuable non-invasive tool in the detection of early atherosclerotic vascular changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
146
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(165 citation statements)
references
References 22 publications
14
146
5
Order By: Relevance
“…Bjällmark et al reported that the possible heterogeneity of the deformation pattern may be further accentuated by atherosclerotic plaque and plaque calcification 16. In agreement with previous studies,15, 16 CAAS measurement using 2D‐ST echocardiography in the present study demonstrated the heterogeneous motion pattern and local variations in compliance of different segments of the ascending aortic wall (Figure 1B and 1C). According to previous investigators,14, 15 we divided the ascending aortic wall into 6 equally sized segments.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Bjällmark et al reported that the possible heterogeneity of the deformation pattern may be further accentuated by atherosclerotic plaque and plaque calcification 16. In agreement with previous studies,15, 16 CAAS measurement using 2D‐ST echocardiography in the present study demonstrated the heterogeneous motion pattern and local variations in compliance of different segments of the ascending aortic wall (Figure 1B and 1C). According to previous investigators,14, 15 we divided the ascending aortic wall into 6 equally sized segments.…”
Section: Discussionsupporting
confidence: 92%
“…However, validity and reproducibility of these methods are limited because of their dependence on the patient's blood pressure 7, 9. In contrast, strain imaging, using 2D ultrasonography with a speckle tracking technique, is a sensitive and reliable method for the assessment of elastic properties of arteries and offers a valuable tool for early identification of atherosclerosis 16. This method provides 2D data that enable researchers to assess the elastic properties of the arterial wall directly9, 16, 27, 35 and show a high sensitivity and good reproducibility 16, 27.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations